Investigation of etiology-specific alterations in the gut microbiota in liver cirrhosis. (2nd December 2021) - Naseri, Mohadeseh; Houri, Hamidreza; Yadegar, Abbas; Asadzadeh Aghdaei, Hamid; Zahiri, Javad
ABSTRACT: Background: Liver cirrhosis can develop as a consequence of many chronic liver diseases, such as viral hepatitis, fatty liver, or alcohol abuse. There are insufficient data on whether the different etiologies of liver cirrhosis could be related to the specific gut microbial alterations. This study aimed to compare the diversity and composition of the gut microbiota in different etiologies of liver cirrhosis. Methods: In the current study, the authors used three previously reported metagenomic datasets to investigate the fecal microbiota in cirrhotic patients with distinct etiologies. Microbial diversity and bacterial taxonomic composition were investigated bioinformatically in cirrhotic patients with different etiologies. Results: The analysis revealed no evidence of a significant difference in microbial diversity between cirrhotic patients with different etiologies. At the family level, cirrhotic patients with nonalcoholic fatty liver disease (NAFLD) showed a significantly higher abundance of the Enterobacteriaceae family and the related genera. Conclusion: No robust microbial signal was found to differentiate between various underlying etiologies in cirrhotic patients. The data indicate that the geographical origin of cirrhotic patients could affect the composition of the gut microbiome, the effect of which obscures the impact of the etiology of cirrhosis.